Properties and mechanism of phase-change bitumen with polyurethane shell microencapsulated as modifier - Hui-Ru Wang; Yan-Min Wang; Fei Huang; Zi-Hua Zhang; Xi-Long Wang; Hui-Sheng Liu; Xiang-Ze Kong; Fan-Jun Ning; Fan-Nan Jia (Case Studies in Construction Materials, 2023)
This study focuses on the thermal performance properties and mechanism by which polyurethane Microencapsulated phase-change materials (MEPCMs) modify bitumen. The MEPCMs were prepared via interfacial polymerization, with butyl stearate as the core material and polyurethane as the shell material. Bitumen modified by MEPCMs was prepared using a high-speed shearing method. The modification mechanism was investigated using various microscopic and macroscopic techniques, including Atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR), and Fluorescence microscope (FM) tests. The research results show that MEPCMs can improve the rheological properties, anti-aging properties, and temperature sensitivity of the modified bitumen. FTIR analysis indicates that there are no chemical reactions between MEPCMs and bitumen, while AFM topography shows the appearance of smaller ''bee structures'' on the surface of MEPCMs-modified bitumen. Additionally, the research reveals that MEPCMs can be evenly distributed in the base bitumen. Finally, the maximum temperature difference between the control bitumen and 3% MEPCMs-modified bitumen is 13.9 ℃.